2018
DOI: 10.1002/mp.13265
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific alert criteria to detect patient‐related errors with 3D EPID transit dosimetry

Abstract: Purpose: To assess the sensitivity of various EPID dosimetry alert indicators to patient-related variations and to determine alert threshold values that ensure excellent error detectability. Methods: Our virtual dose reconstruction method uses in air EPID measurements to calculate virtual 3D dose distributions within a CT data set. Patient errors are introduced by transforming the plan-CT into an error-CT data set. Virtual patient dose distributions reconstructed using the plan-CT and the error-CT data set are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…In practice, and owing to the presence of false positives and false negatives, EIVD systems are typically implemented in combination with other patient-specific QA systems. False negatives are of particular importance because they hide relevant errors that are not being detected [82]. To detect these errors, EIVD must be used in combination with image-guided radiation therapy procedures such as CBCT visualization and/or CBCT-based dose calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, and owing to the presence of false positives and false negatives, EIVD systems are typically implemented in combination with other patient-specific QA systems. False negatives are of particular importance because they hide relevant errors that are not being detected [82]. To detect these errors, EIVD must be used in combination with image-guided radiation therapy procedures such as CBCT visualization and/or CBCT-based dose calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental acquisition of EPID measurements to produce such samples is typically a cumbersome process, which explains why there are only a few studies on the topic in the IVD literature [78][79][80][81]. Recently, use has been made of synthetic EPID images to eliminate the need for phantom error introduction and positioning [82]. Another alternative is to model possible errors by introducing modifications in the TPS [83].…”
Section: Specificity and Sensitivitymentioning
confidence: 99%
“…It has been demonstrated that this approach can detect patient setup errors as well as uniform contour changes. 16 An analysis technique recently introduced in a doctoral dissertation, originally for pretreatment IMRT QA comparisons, gradient dose segmented analysis (GDSA), has been shown to predict changes in PTV D mean from using only measurements from IMRT QA diode arrays without the need for reconstruction methods. 17 The work outlined here makes use of GDSA to analyze EPID transit images.…”
Section: Introductionmentioning
confidence: 99%
“…Since the reconstruction is performed on planning CT data, the goal of this metric is not an accurate determination of the dose delivered to the patient but a method to detect clinically relevant errors. It has been demonstrated that this approach can detect patient setup errors as well as uniform contour changes 16 …”
Section: Introductionmentioning
confidence: 99%
“…38 Second, the dose delivered to the patient during treatment is affected by patient setup variations and patient anatomical changes. 39 Last, another limitation of the algorithm is that it uses the planning CT as patient anatomy model for dose reconstruction. To better cope with the challenge of patient variations, more accurate results are expected once the daily patient anatomy is used in the reconstruction.…”
Section: Transit Epid Non-transit Epidmentioning
confidence: 99%